Examining the Relationship Between Innovation Characteristics and Extension Support When Using Jajar Legowo as an Agricultural Innovation - Putra, Rizki Aditya; Sadono, Dwi (Jurnal AGRISEP, 2024)
The Jajar Legowo, as an agricultural technique innovation, has been introduced to farmers in Pangkal Jaya Village for quite some time. However, its implementation has not consistently followed the recommendations despite its proven ability to increase rice production. This research aims to review the adoption of the "Jajar Legowo" innovation in Pangkal Jaya Village, Bogor Regency, by analyzing the relationship between extension support and the farmer's perception of the innovation characteristics with implementing the innovation system. The research uses a survey method to collect quantitative data, supplemented by qualitative data obtained through in-depth interviews, observations, and literature review. The study found that the level of Jajar Legowo innovation implementation in Pangkal Jaya Village is relatively high and significantly related to extension support and farmers' perceptions of the characteristics of the Jajar Legowo planting technique. The effectiveness of the extension methods and content makes farmers quickly understand how to use the Jajar Legowo planting system, even though the extension media is less varied and the intensity of the extension is relatively low. Farmers assess Jajar Legowo as an agricultural innovation that is profitable, simple, and in accordance with farmers' needs, and the results can be observed. However, Jajar Legowo is challenging to implement because of the limited land available to farmers, requiring several adaptation strategies.